Parametric analysis of the coating thickness development of electrophoretically deposited carbon nanotube coatings - Timothy MacLucas; Silas Schütz; Sebastian Suarez; Frank Müller; Frank Mücklich (Carbon Trends, 2023)
In this study, the coating thickness evolution of pristine and oxidized carbon nanotubes (CNT) on stainless steel substrates is investigated. Potentiostatic electrophoretic deposition (EPD) is used as a coating technique with two different additives, triethylamine (TEA) and magnesium nitrate hexahydrate (Mg-Nit). Moreover, the depositions are conducted at different voltages (50, 100 and 150 V). Confocal laser scanning microscopy is used to determine the thickness of the CNT depositions after 1, 2, 5, 10, 20 and 30 min. Furthermore, the ability of Hamaker's law to accurately predict coating thickness development is investigated for the thickness evolution on stainless steel.Independent of the additive, the results show that higher voltages lead to increased deposition rates. Comparing the two additives, Mg-Nit generally allows for a higher CNT deposition rate than TEA and forms thicker layers. Coating thickness development can be approximated as linear during the initial 5 min with Mg-Nit and during the initial 20 min with TEA. Finally, Hamaker's law allows for a fairly accurate approximation for the thickness development of CNT coatings with TEA on stainless steel.